(untitled) (Móin-Móin - Revista de Estudios sobre Teatro de Formas Animadas, 2019)
This article captures the one-hour presentation, discussions and interactive dialogue at the conference: The theatrical function of the image and its relation to the other elements of staging. Pedagogical approach. The main idea of the conference is that nowadays the context of performing arts claims a reconsideration of the pedagogical approach of the profession of theatre director. I will recall how the “job” of theatre director has emerged in 19th century as a logical result of the industrialisation. Bringing electric light into theatre auditoriums, building bigger theatres with wider stages, the appetence of the public for elaborate and realistic staging using 3D props and complicated machineries – all this imposed the necessity of a man who has or develops the skills and knowhow of staging. And that’s how the history of the world theatre was re-written in the 20th century – The Century of the Director. Moreover, the two most influential theatre people of the last century where both directors and professors: Konstantin Stanislavsky and Bertolt Brecht. But what about our 21th century? Is theatre still “a play ground” for the directors? My theory is that the performing arts today are erasing the “traditional” patterns of theatre makers under the pressure of the new role that theatre is claimed to perform in society. The theatre of Digital Era needs to have the same “pixeled” structure as every other human creation. That’s why I strongly believe that the pedagogy of theatre must be reconsidered and reorganized having as its central idea the dichotomy between the dramatic and the post-dramatic structure of the play. After all, as Peter Brook said: “A play is a play.” As support for demonstration and discussions I will use Meyerhold’s theory on how to construct a performance, Schlemmer’s diagram on types of performances, Brecht’s remarks on dramatic theatre vs. epic theatre, Lehmann’s theory on post-dramatic theatre and Erika Fischer-Lichte’s arguments on transformative aesthetics. I will use images from shows staged by outstanding theatre directors, which marked or/and are marking how we make and look at theatre today.